Antitumor effects of citrinin in an animal model of Sarcoma 180 via cytogenetic mechanisms - Filho, José Williams Gomes de Oliveira; dos Santos Andrade, Teresinha de Jesus Aguiar; de Lima, Rosália Maria Tí´rres; dos Reis, Antonielly Campinho; Hameed, Aneela; Santos, José Victor de Oliveira; Afzal, Muhammad Inam; de Menezes, Ag-Anne Pereira Melo; de Alencar, Marcus Vinícius Oliveira Barros; Silva, Dulce Helena Siqueira; Dias, Ana Carolina Soares; Ferreira, José Roberto de Oliveira; et al. (Cellular and Molecular Biology, 2020)
Citrinin (CIT) is a cytotoxic, hepatotoxic, nephrotoxic and cardiotoxic metabolite obtained from Penicillium citrinum, that has been increasingly searched as an anticancer drug candidate. In this study, we assessed the antitumor effects of citrinin, using cytogenetic biomarkers for genotoxicity in Sarcoma 180 (S-180) ascitic fluid cells of mice. Citrinin, extracted from P. citrinum acetonitrile extract, was characterized by LC-MS. Cytotoxic assessment was done through using comet (alkaline version) and micronucleus assays. In S-180 cells, CI50 of CIT was 3.77 Î¼g/mL, while at 12.5 and 100 Î¼g/mL, CIT was as cytotoxic as doxorubicin (2 Î¼g/mL). At 0.5, 1.0 and 2.0 Î¼g/mL, it induced genotoxicity and mutagenicity in S-180 cells, especially at 2 Î¼g/mL, triggering oxidative damage similar to hydrogen peroxide (10 mM). The antitumor effects were evidenced by a marked increase in S-180 cells apoptosis and necrosis due to clastogenic and/or aneugenic cytogenetic effects (micronucleus formation), as well as by induction of nucleoplasm bridges and nuclear buds, culminating in S-180 apoptosis and necrosis. CIT has potential as drug candidate for antitumor purposesbyinvolving cytogenetic mechanisms.